Using knowledge creatively - Svanborg Rannveig Jónsdóttir 1953- (2009)
This article is about innovation education, a compulsory school subject in Iceland, somewhat similar to design and technology education in England and other countries. Innovation education has been used successfully as a strategy to enhance students´ understanding of technology and science as they research their own environments and invent objects and technologies that they make themselves, rather than only learning ´about´ technology or science. The article describes how two creative science teachers in Iceland have approached innovation education as a subject and as a tool to enhance and develop creativity in children, making use of knowledge from different subjects and from life. The article builds on fieldwork with two compulsory school science teachers and on written documentation, such as the national curriculum. The stories of the teachers and the story of innovation education in Iceland are told, the characteristics of the two teachers described and examples of their teaching introduced and threaded together by the authors own experiences of teaching innovation education in primary school. Svanborg Rannveig Jónsdóttir was a compulsory school teacher for 28 years in a small rural school, currently a Ph.D. student at the School of Education, University of Iceland and her reseasch is about innovation education in Icelandic compulsory schools.